The Appeal Of Advertising And Word Of Mouth To Online Shopping Interests On Shopee Application - raihana daulay; Siti Mujiatun (International Journal Reglement & Society (IJRS), 2021)
Advertising is the determinant of the success of an online sale. The goodness of the image becomes an attraction that generates consumer interest in a product. Similarly, word of mouth as an amplifier of advertising that has attracted customers to immediately make a purchase. Problems in online purchases are often occurring, products that do not match the received, so there are comments that raise doubts consumers to buy. This study aims to find out the Effect of Advertising And Word Of Mouth On Online Shopping Interests Through Shopee Application. The population in this study is anyone who has shopped using shopee app in the last 1 year. Data analysis techniques use multiple linear regressions, tests, classic assumptions, t-tests, F-tests and determination coefficients. The results showed that advertising has a positive and significant effect on shopping interests on shopee apps, Word of mouth partially has a positive and significant influence on shopping interests. Ads and word of mouth simultaneously have a positive and significant effect on shopping interests using the shopee app